Identifikasi Spesies Meloidogyne pada Wortel berdasarkan Sikuen Nukleotida - Halimah Halimah; Supramana Supramana; Gede Suastika (Jurnal Fitopatologi Indonesia, 2014)
Root-knot nematodes (RKN), Meloidogyne spp., were reported as the cause of carrot branched tuber on several vegetable production areas in Central and East Java. Species identification by molecular approach was conducted using infected carrot tubers from Agropolitan Cianjur, West Java. DNA was extracted from female nematodes and amplified using PCR with species specific primers (Fjav/Rjav for M. javanica, Far/Rar for M. arenaria, and Finc/Rinc for M. incognita) and multiplex primer (M. hapla, M. chitwoodi, and M. fallax). PCR product were sequenced without cloning. Based on nucleotide sequences, two species RKN were found associated with branched tuber disease of carrot in Agropolitan Cianjur, i.e M. javanica and M. hapla. Phylogenetic analysis showed that M. javanica from Cianjur was closely related to RKN from China with the homology level of 91.9%, whereas nucleotide sequence of M. hapla from Cianjur had high homology level (99.4% to 100%) with isolates from Swiss, USA, UK, and China.